VALIDATING CAREGIVER-CHILD INTERACTIONS SCALE (CCIS) AMONG GHANAIAN EARLY CHILDHOOD PRACTITIONERS: A PILOT STUDY - NYARKO, NANA YAA A. (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
To ensure quality in the rendering of early childhood development and care services, guidelines are in place to ensure physical and structural quality expectations are followed in Ghanaian early childhood institutions. However, it is not known what processes or interactions caregivers engage in to enhance the development of the children in their care. The Caregiver-Child Interaction Scale (CCIS) assesses child development on the three developmental domains (i.e., physical, cognitive, and socio-emotional) and captures child development and wellbeing quality based on the interactions (processes) adopted by caregivers (teachers). This paper explores the factor structure of the CCIS when used to assess the process quality in some selected early childhood care and development facilities in Ghana. Seventy-six percent (76%) of the 103 caregivers observed obtained minimal scores and their interactions resulted in basic (minimal) support to the development and wellbeing of the children in their care. The CCIS demonstrated a positive but weak correlation (.26) with perceived interactions scale intended to assess similar dimensions of child development and wellbeing. Further, the CCIS reported 3 factor loadings that mimicked the three developmental domains.